2013
DOI: 10.1002/aoc.3053
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship of N‐heterocyclic carbene–Pd(II)–imidazole complexes in Suzuki–Miyaura coupling between 4‐methoxyphenyl chloride and phenylboronic acid

Abstract: A series of N-heterocyclic carbene-PdCl 2 -imidazole [NHC-Pd(II)-Im] complexes were synthesized and the structure of most of them was unambiguously determined by X-ray single-crystal diffraction. The structure-activity relationship of these complexes was investigated for the Suzuki-Miyaura coupling between 4-methoxyphenyl chloride and phenylboronic acid, and the effect of the NHCs and Im moieties were fully discussed. The sterically hindered IPr-based complex showed the highest catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Complexes 4b, 4c and 4e were prepared by procedures reported in the literature. 10,11 Spectroscopic data match those reported in the literature.…”
Section: Synthesis Of Pd-nhc Complexessupporting
confidence: 83%
See 1 more Smart Citation
“…Complexes 4b, 4c and 4e were prepared by procedures reported in the literature. 10,11 Spectroscopic data match those reported in the literature.…”
Section: Synthesis Of Pd-nhc Complexessupporting
confidence: 83%
“…00, 151.54, 146.77, 137.49, 135.24, 130.36, 125.13, 124.15, 124.12, 28.86, 26.43, 23.38. Synthesis of 4c. 11 On a benchtop, a vial equipped with and a stir bar was charged with PdCl2 (17.7 mg, 0.10 mmol), IPrHCl (0.12 mmol), K2CO3 (0.10 mmol), and 1-methylimidazole (0.40 mmol), placed under a positive pressure of argon, and subjected to three evacuation/backfilling cycles under high vacuum. THF (0.15 M) was added, the reaction mixture was placed in a preheated oil bath at 65 °C and stirred for 20 h at 65 °C.…”
Section: Synthesis Of Pd-nhc Complexesmentioning
confidence: 99%
“…In addition, both of them are longer than that of its i-propyl analogue, that of which are 1.960(3) and 2.093(3) Å, respectively [1]. Therefore, it maybe draw the conclusion that stronger σ e ect exsits in the latter complex, and may be the result of its higher catalytic activity [13].…”
Section: Discussionmentioning
confidence: 97%
“…For instance, the synthesis of [1,3-bis(2,6-diisopropylphenyl)-1H-imidazol-2(3H)-ylidene]palladium complex, from easily available starting materials in a one-pot procedure was reported [1]. In addition, the applications of this complex have been fully investigated in Suzuki-Miyaura coupling [2,[11][12][13][14][15][16][17][18], C-N coupling [1,[19][20][21], α-arylation of carbonyl compounds [22][23][24][25][26], Hiyama coupling [27], Mizoroki-Heck reaction [28] and direct C-H bond functionalization of heteroaromatic compounds [29][30][31][32][33]. As its analogue, initial studies on the catalytic activity of the title complex showed that it is also an e cient catalyst in the C-N coupling between primary and secondary amines with aryl chlorides at very low catalyst loadings, implying that the anions on the complex may have no e ect on the catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The title product was prepared by modi cation of the literature known methods [1,2]. Under a nitrogen atmosphere, 1,3-bis(2,6-diisopropylphenyl)-1H-imidazolium bromide (0.7 mmol), palladium acetate (0.7 mmol), sodium bromide (0.7 mmol), potassium carbonate (0.7 mmol), tetrahydrofuran (5.0 mL) and 1-methylimidazole (2.5 mmol) were successively added into a Schlenk tube.…”
Section: Source Of Materialsmentioning
confidence: 99%